An assessment of Actionaid Ghana rights- based approach to poverty reduction. a case of Asutifi District in the Brong Ahafo Region - Abaa, John (2016)
A thesis submitted to the School Graduate Studies, Kwame Nkrumah University of Science and Technology, in Partial fulfillment of the requirements for the Award of Degree of Master of Science Development Policy and Planning, 2015